Impact of a food supplement containing Citrus limon L. Osbeck and Vitis vinifera L. extracts, hesperidin and chromium in combination with an isocaloric diet on glucose and lipid metabolism in subjects with impaired fasting blood glucose: a single-center, controlled, randomized, parallel-arm, double-blind clinical trial - Di Minno, Alessandro; Morone, Maria Vittoria; Buccato, Daniele Giuseppe; De Lellis, Lorenza Francesca; Ullah, Hammad; Borromeo, Luca; Cerqua, Angela; Piccinocchi, Roberto; Greco, Agostino; Santonastaso, Salvatore; Larsen, Danaé S.; El-Seedi, Hesham; et al. (Frontiers in Nutrition, 2025)
IntroductionImpaired fasting glycemia (IFG) puts carriers at a significantly higher risk of developing type 2 diabetes and cardiovascular disease. Lifestyle changes, such as increased physical activity and a healthy diet rich in fiber and low in sugar, can often reverse prediabetes and significantly reduce the risk of progressing to type 2 diabetes metabolic disorders, especially diabetes (1).MethodsThis randomized clinical trial aims to evaluate the efficacy and tolerability of a food supplement (FS) containing Citrus limon L. Osbeck and Vitis vinifera L. extracts, hesperidin from Citrus sinensis L. Osbeck, and chromium, in individuals with impaired fasting blood glucose , with the final goal of investigating whether the use of a combination of ingredients, known to exert their positive effects through different mechanisms of action, is a helpful strategy for improving glucose metabolism. Sixty-two subjects (aged 18–75 years) with IFG levels ranging from 100–to 125 mg/dL were assigned to receive either a FS or a placebo (n = 31 per group) for 6 months, in combination with an isocaloric diet. Participants took two tablets daily. Biochemical parameters related to glucose and lipid metabolism and markers of liver and kidney functionality were evaluated at baseline (T0), and after 3 and 6 months.ResultsThe treatment group showed a significant improvement in fasting glycemia after 3 months, with normalization of glucose levels (P < 0.001 vs T0), unlike the placebo group. Statistically improvements were also observed in HDL and LDL cholesterol and triglycerides.DiscussionDaily intake of the tested FS in combination with an isocaloric diet significantly improved glucose and lipid metabolism, suggesting that the combination of ingredients with different mechanisms of action can be considered a valuable strategy for improving impaired fasting blood glucose and lipid profiles.Clinical trial registrationwww.isrctn.com, ISRCTN15062713.